The effects of stocking rate, residual sward height, and forage supplementation on forage production, feeding strategies, and productivity of milking dairy cows - Ortega, Gastón; Berberian, Natalia; Chilibroste, Pablo (Frontiers in Animal Science, 2024)
The intensification process in Uruguayan dairies over the last 30 years has involved increases in stocking rate (SR) and individual milk production. This research aimed to compare biophysical indicators along with the associated feeding strategies for Holstein–Jersey crossbred dairy cow systems. The comparison was conducted in farmlets representing a typical Uruguayan pasture-based dairy system on a grazing area. The study spanned from 2017 to 2019, combining 1.5 or 2.0 milking cows per hectare (SR), with two different residual sward heights (RH)—low (LR) and high (HR). These combinations resulted in four treatments: 1.5 LR, 1.5 HR, 2.0 LR, and 2.0 HR. A total of 96 cows were randomly allocated to each treatment based on parity, body weight (BW), and body condition score (BCS) for the years 2017, 2018, and 2019. The response variables per hectare were analyzed using a linear mixed model, including SR, RH, their interaction effect, year, and paddock as a repeated measurement. Results show that forage production did not differ between treatments, and forage directly harvested by cows was affected by SR, as well as milk and solids productivity. An interaction effect was detected between SR and RH on milk and milk solids production where 2.0 HR was higher than 2.0 LR, but treatments on SR 1.5 were not different between them. The consumption of concentrate, forage, and conserved forage per hectare was influenced by the level of SR. However, individual milk production was not influenced by SR or RH. Dry matter intake were affected by SR where 2.0 HR had higher consumption than 1.5 LR and 1.5 HR but was not different from 2.0 LR. The concentrate DMI per cow was not different between treatments, while the conserved forage DMI per cow was affected by SR and higher for SR 2.0 than that for SR 1.5. These combinations of feed determined varying proportions of time allocated for grazing, which were influenced by the SR and RH. This research highlights different approaches to enhance the competitiveness of Uruguayan grazing systems through improvements in forage harvest.